2013
DOI: 10.1371/journal.pone.0071507
|View full text |Cite
|
Sign up to set email alerts
|

Altered Pattern of Spontaneous Brain Activity in the Patients with End-Stage Renal Disease: A Resting-State Functional MRI Study with Regional Homogeneity Analysis

Abstract: PurposeTo investigate the pattern of spontaneous neural activity in patients with end-stage renal disease (ESRD) with and without neurocognitive dysfunction using resting-state functional magnetic resonance imaging (rs-fMRI) with a regional homogeneity (ReHo) algorithm.Materials and Methodsrs-fMRI data were acquired in 36 ESRD patients (minimal nephro-encephalopathy [MNE], n = 19, 13 male, 37±12.07 years; non-nephro-encephalopathy [non-NE], n = 17, 11 male, 38±12.13 years) and 20 healthy controls (13 male, 7 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 45 publications
7
54
0
Order By: Relevance
“…Moreover, this region was found anatomically altered in MOH patients (5). FC of the precuneus is known to be lateralized (29) and the right and left precuneus are differentially sensitive to aging (30) and diseases (31,32), with the left precuneus being more sensitive in right-handed subjects. We thus focused all analyses on left precuneus as all our subjects were right-handed.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Moreover, this region was found anatomically altered in MOH patients (5). FC of the precuneus is known to be lateralized (29) and the right and left precuneus are differentially sensitive to aging (30) and diseases (31,32), with the left precuneus being more sensitive in right-handed subjects. We thus focused all analyses on left precuneus as all our subjects were right-handed.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…However, this study only focused on the structural and functional connectivity changes in the default mode network 1 month after kidney transplantation. The effects of ESRD may be more global (20), and the potential involvement of other resting-state subnetworks warrants investigation. Thus, the purpose of this investigation is to examine the recovery patterns of seven resting-state subnetworks in patients with ESRD after kidney transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we found decreased long-and short-range FCD in frontal (mainly) and parietal lobe. Many studies have found functional alteration of frontal and parietal lobe in patients with ESRD (Harciarek et al 2012;Liang et al 2013). Frontal and parietal lobe dysfunction is characterized clinically by decreased spontaneity, initiative, insight, judgment, abstraction, perseverance and response inhibition (Hirakata et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Especially, resting-state fMRI (rsfMRI) has attracted more attention as a powerful tool to study brain activity in patients at resting state (Snyder and Raichle 2012). To our knowledge, only a few studies on neuropathological mechanism of cognitive impairment in patients with ESRD were carried out by using rs-fMRI (Liang et al 2013;Li et al 2014;Ni et al 2014). Liang et al found progressively decreased regional homogeneity in the default mode network (DMN), frontal and parietal lobes in patients with ESRD (Liang et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation